Activity Stabilization in a Population Model of Working Memory by Sinusoidal and Noisy Inputs - Novikov, Nikita; Zakharov, Denis; Moiseeva, Victoria; Gutkin, Boris (Frontiers in Neural Circuits, 2021)
According to mechanistic theories of working memory, information is retained as stimulus-dependent persistent activity of cortical neural networks. Yet, how this activity is related to modulations of collective oscillatory activity observed in working memory tasks remains a largely open issue. In this paper, we focus on interactions between externally generated sinusoidal gamma-band oscillations, input noise, and the dynamics of a firing rate model describing a system of two excitatory-inhibitory neural circuits with mutual excitation. The system was parametrized to have a stable background state and a metastable active retention regime with gamma-band resonance, so it demonstrated long-lasting stimulus-induced transient firing rate elevation, which also carried gamma-band quasi-oscillations in the presence of noise. We started from a single-circuit system and demonstrated that either gamma-band or noise input alone could stabilize the active regime, supporting proper memory retention. In the two-circuit system, the stabilizing effect of external inputs depended on the type of inter-circuit connections. In the case of fast connections, in-phase gamma-band input and common noise delivered to the circuits provided better stabilization than anti-phase input and independent noise. In the case of slow connections, anti-phase input was slightly more effective, without difference between in-phase and anti-phase oscillatory inputs. Importantly, in each case there was a range of oscillation amplitudes, in which the gamma-band input stabilized memory retention with different efficiency, depending on the common or independent character of the noise. Based on the results obtained for the two-circuit system, we discuss how the described mechanisms may impact memory retention in multi-circuit schemes. Assuming that common noise reflects similar information tuning of neural circuits, we hypothesize that gamma-band input may produce selectivity increase in local clusters, while slow connections between distant clusters may provide a basis for gamma-induced functional binding.